2015
DOI: 10.1038/pr.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-linked kinase mediates CTGF-induced epithelial to mesenchymal transition in alveolar type II epithelial cells

Abstract: Background: Overexpression of connective tissue growth factor (CTGF) in alveolar type II epithelial (AT II) cells disrupts alveolar structure, causes interstitial fibrosis, and upregulates integrin-linked kinase (ILK). Whether CTGF-ILK signaling induces epithelial to mesenchymal transition (EMT) in AT II cells is unknown. Methods: Transgenic mice with targeted overexpression of CTGF in AT II cells were generated utilizing the surfactant protein C (SP-C) gene promoter and doxycycline-inducible system. AT II cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Second, it is unclear how CTGF activates β-catenin signaling in the neonatal lung. Our previous in vitro Articles studies have provided evidence that overexpression of CTGF in AT II cells induces EMT via ILK, suggesting an autocrine mechanism via integrin pathway (31). We have also showed that LRP5/6 is important in hyperoxia activation of β-catenin signaling in vascular smooth muscle cells but not in alveolar epithelial cells of the neonatal lung (39).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Second, it is unclear how CTGF activates β-catenin signaling in the neonatal lung. Our previous in vitro Articles studies have provided evidence that overexpression of CTGF in AT II cells induces EMT via ILK, suggesting an autocrine mechanism via integrin pathway (31). We have also showed that LRP5/6 is important in hyperoxia activation of β-catenin signaling in vascular smooth muscle cells but not in alveolar epithelial cells of the neonatal lung (39).…”
Section: Discussionmentioning
confidence: 64%
“…In CTGF transgenic lungs, part of the β-catenin nuclear translocation was detected in AT II cells (31). Furthermore, overexpression of CTGF induces β-catenin nuclear translocation and disrupts alveolar-like cyst formation in cultured AT II cells (12,31). In this study, we showed that administration of a β-catenin inhibitor significantly improved alveolarization in CTGF transgenic lungs.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Figure S4 A-B). CTGF was already linked to MET in the pathogenesis of brotic diseases (e.g., renal, myocardial, pulmonary brosis; [43,44]. We could treat zebra sh for 24 h only as zebra sh treated further showed behavioral alterations (e.g., changes in activity, schooling behavior, social interaction) and, thus, excluded from the study.…”
Section: Discussionmentioning
confidence: 99%
“…ILK is a serine threonine protein kinase that is involved in regulating integrin‐mediated processes such as cell adhesion, proliferation, and extracellular matrix deposition and is a mediator of EMT . The only study exploring the role of ILK in BLM‐induced pulmonary fibrosis identified that although ILK expression was not altered and did not directly regulate pulmonary fibrosis, it mediated its profibrotic effect through the upregulation of vimentin .…”
Section: Discussionmentioning
confidence: 99%